The gram-negative bacterium Escherichia coli as a model for testing the effect of carbonic anhydrase inhibition on bacterial growth - Viviana De Luca; Vincenzo Carginale; Claudiu T. Supuran; Clemente Capasso (Taylor & Francis Group, 2022)
Carbonic anhydrases, catalysing the reversible CO2 hydration reaction, contribute in all living organisms to the maintenance of stable metabolic functions depending on intracellular concentrations of carbon dioxide, bicarbonate, and protons. Recent studies have examined how CAs affect bacterial lifecycle, considering these enzymes druggable targets due to interference with their activities by using inhibitors or activators. Here, we propose Escherichia coli cells as a model for testing the effect of acetazolamide (AZA), a potent CA inhibitor, on bacterial survival by evaluating E. coli growth through its glucose consumption. AZA, at concentrations higher than 31.2 µg/mL, was able to impair E. coli growth and glucose uptake. AZA is a good inhibitor of the two recombinant E. coli CAs, the β-CA CynT2, and the γ-CA EcoCAγ, with KIs of 227 and 248 nM, respectively. This study provides a proof-of-concept, low-cost method for identifying effective CA inhibitors capable of impairing bacterial metabolism.